2016
DOI: 10.1017/ice.2016.86
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an Automated Surveillance to Detect Surgical-Site Infections in Patients Undergoing Total Hip and Knee Arthroplasty in Brazil

Abstract: In this retrospective study, we compared automated surveillance with conventional surveillance to detect surgical site infection after primary total hip or knee arthroplasty. Automated surveillance demonstrated better efficacy than routine surveillance in SSI diagnosis, sensitivity, and predictive negative value in hip and knee arthroplasty. Infect Control Hosp Epidemiol 2016;37:991-993.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 9 publications
0
12
1
Order By: Relevance
“…From 2010 on, the numbers of publications increased and peaked in 2014. Contributions originating from South America [56] and Asia [3,24,50,67,68,77] showed that by that time EASS of HAI had adopters worldwide.…”
Section: Timeline and Geographical Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…From 2010 on, the numbers of publications increased and peaked in 2014. Contributions originating from South America [56] and Asia [3,24,50,67,68,77] showed that by that time EASS of HAI had adopters worldwide.…”
Section: Timeline and Geographical Distributionmentioning
confidence: 99%
“…Following microbiological data, antibiotic prescriptions data are the second most used variable in EASS algorithms (38 of 78 studies) and, when not combined with microbiological data, most often found in combination with ICD coding [12,16,36,56].…”
Section: Antibioticsmentioning
confidence: 99%
“…[8][9][10] Such semiautomated electronic surveillance systems have been reported to reduce the workload for chart reviews while maintaining a high sensitivity of SSI detection for specific surgical procedures such as total hip and knee arthroplasty. [11][12][13][14][15] However, previous studies have been limited to certain types of surgery. The goal of this study was to verify the validity of semiautomated SSI surveillance using electronic screening algorithms in 38 categories of surgery.…”
mentioning
confidence: 99%
“…This latter observation also held true for the other types of surgery. In previous studies, data on antibiotics were added to enhance case findings, [17][18][19] but this addition was not essential to this study, and the same held true for data on radiological interventions. Although additional information could be used to optimize algorithm performance, it is feasible to develop well-performing algorithms that rely solely on microbiology results, admission and discharges dates, and procedures codes.…”
Section: Discussionmentioning
confidence: 99%